Association of lifestyle and overweight in medical residents at a national hospital - Cuba, Jhon (2011)
Background: In recent years weight excess has increased worldly. The physician is part of society and the first image in health care and should be adequately healthy. Objectives: To correlate lifestyle and overweight in medical residents. Design: Correlation, observational, prospective, transversal study. Setting: Hospital Nacional Daniel Alcides Carrion, Lima, Peru. Participants: Medical residents. Interventions: A sample of 34 medical residents 25 through 60 year-old was studied. Weight and height were obtained for body mass index and a lifestyle survey was applied. Main outcome measures: Lifestyle relation to weigh excess. Results: From 34 residents 88% were male and 12% female; average age was 31,5 ± 7,5; 53% presented overweight and 21% obesity. In relation to lifestyle subjects spent 9 minutes for breakfast, 26 minutes for lunch and 27 for dinner; 88% and 82% respectively consumed fruits and vegetables below recommendations; 71% had snacks between meals and 69% of them were overweight; 46% of those overweight preferred high seasoned foods and 65% ate foods less than two hours before sleeping; 91% continued working after night calls; 74% did not have programmed physical activity and 65% considered himself stressed. Conclusions: There existed 74% weight excess in this hospital medical residents, but it did not correlate with lifestyle.